Robotic animals as new tools in rodent neuroscience research: proposed applications of zooinspired robots for mouse behavioral testing - d’Isa, Raffaele (Frontiers in Behavioral Neuroscience, 2025)
Bioinspired robots are machines which reproduce structural or functional features of a living organism. In particular, the bioinspired robots which reproduce features of animals can be more specifically defined as zooinspired robots. Currently, the applications of animal robots are various and range across different fields, such as, for instance, nature conservation, search and rescue of humans after natural or man-made disasters, exploration of extraterrestrial environments and robotic pets for elderly people under care for dementia. Several animal species have been imitated up to now, from lizards to butterflies, and from fish to dogs. Animal robots used to investigate the social behavior of an animal species through animal-robot interactions are called ethorobots. Intriguingly, ethorobots are able to reproduce in the laboratory behaviors that are generally produced spontaneously in nature and are difficult or impossible to evoke and modulate in captive animals, which makes these animal robots particularly useful tools for experimental ethology and ethological neuroscience. Rodents, primarily mice and rats, are the most common animal model in biomedical research. Coherently with the importance of these species for scientific research, robotic mice and rats have been attracting increasing efforts in bioinspired robotics over the course of the past five decades. The technological advancement of animal robots will make their employment for scientific research increasingly useful. However, clear experimental applications of animal robots should be identified in order to challenge engineers to design robots that can serve these experimental scopes. In the present work, we will describe possible practical applications of robotic animals for mouse behavioral testing across six different behavioral domains, namely courtship, parental care, antipredatory behavior, helping behavior, predation and territory defense-related aggression. In particular, we will outline how robotic animals could be employed to interact with living mice in a series of specific tests of social behavior. Finally, in the conclusion we will consider the ethical and epistemological advantages of the use of robotic animals in behavioral neuroscience. Indeed, robotic animals can benefit scientific research on social behaviors both in terms of optimized animal welfare of the tested subjects and of extended opportunities of experimental designing due to an unprecedented control over the independent variables.